(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
In recent decades the subject of "handwritten authentication verification" has been investigated extensively, although there is still an open research issue. People are familiar with stylus and paperwork for legal transaction certification and approval. Due to the expansion of the usage of handwritten authentications, it is necessary to identify authentications by a person manually. Authentication is a social biometric which is defined by a social characteristic that a person learns over time and becomes his unique identity. This article explains the significance of the offline system and gives an overview of several methods in many areas. As this is a region under consideration, the overview deals with a number of examples. The objective of an independent confirmation system is to distinguish whether a given authentication can be certified or duplicated. The result was a tough task in particular in the offline (static) scenario, where the dynamic data about the objectivism process is not available. Although extensive research has been done in this field but there are more opportunities of more research in future.